2007
DOI: 10.1007/s11748-006-0066-6
|View full text |Cite
|
Sign up to set email alerts
|

Floating thrombus in the ascending aorta

Abstract: Floating thrombus in the ascending aorta is an uncommon source of embolism. We report a case of a 61-year-old man who was admitted to our hospital for transient brain ischemic attack. Transesophageal echocardiography showed a floating mass on the sinotubular junction. We started anticoagulation therapy immediately and performed surgical removal of the mass 5 days after the admission. Postoperative course was uneventful. He is now in good health and has no sign of recurrence. The etiology of this case is unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Ito et al (8) reported a case of the women receiving hormone replacing therapy, acute myocardial infarction and aortic thrombus located near the left coronary ostium. Several studies reported cases of aortic thrombus without any known etiology (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ito et al (8) reported a case of the women receiving hormone replacing therapy, acute myocardial infarction and aortic thrombus located near the left coronary ostium. Several studies reported cases of aortic thrombus without any known etiology (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment modalities have been described in different forms and with variable success including thromboaspiration and surgery (5,9,17), thrombolysis (18), anticoagulate therapy alone (13). Exclusion of FFT with endovascular stent graft as a minimally invasive therapeutic option has been recently reported (20,21), however its role has not been fully established yet, regarding the long-term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The operation was performed 5 days after admission despite evidence of splenic embolization during the clinical course. 1 Even though the size of the thrombus was getting smaller with anticoagulation, we believe that surgery should have been performed earlier. Some previous reports have shown catastrophic consequences of a fl oating thrombus in the ascending aorta, such as acute myocardial infarct (AMI) and cerebrovascular accident (CVA).…”
Section: Regarding "Floating Thrombus In the Ascending Aorta" Hidetakmentioning
confidence: 94%
“…1 We congratulate them on their excellent result. We thoroughly agree with their prompt and aggressive workup, including transesophageal echocardiography, to detect a source of embolism.…”
mentioning
confidence: 93%
“…Za zmínku stojí několik případů, kde příčina vzniku trombu v nativní ascendentní aortě nebyla spolehlivě vysvětlena. [3][4][5][6][7][8] První dokumentovaný případ je z roku 1993 popsaný autory Farah a Hawawini, kdy trombus ascendentní aorty byl zdrojem mozkové embolizace. 3 Později Pousios a spol.…”
Section: Diskuse a Závěrunclassified